Kultywując sztukę umierania. W;t Margaret Edson – pomiędzy dramatem a filmem - Ziółkowski , Grzegorz (Przestrzenie Teorii, 2021)
As death returned to make its mark on the world with the COVID-19 pandemic and, consequently, resurfaced in the social imaginary, we have found ourselves once again full-throatedly asking questions about what it means to die well. These issues lie at the heart of W;t, an American play penned in the early 1990s by Margaret Edson, which could be situated alongside other fictional and true stories that “provide social scripts for dying” (Knox). The play might also be viewed as a modern reference to the medieval tradition of ars bene moriendi and the morality plays linked with that tradition in a symbiotic, synergistic manner. The essay attempts to demonstrate that the meaning underlying Edson’s play (and its television adaptation of 2001) derives primarily from its grappling with the subject of human’s agency in the face of the inevitable. In its close reading of the play, the essay moves between the text, first published in print in 1999, and the screen, to best tap into the interpretive potential of comparing the drama and its film adaptation.